2022
DOI: 10.3390/molecules27175377
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Driven Structural Order of Oligo(Ethylene Glycol)-Terminated Alkanethiol Monolayers on Au(111) Prepared by Vapor Deposition

Abstract: To probe the effects of deposition temperature on the formation and structural order of self-assembled monolayers (SAMs) on Au(111) prepared by vapor deposition of 2-(2-methoxyethoxy)ethanethiol (CH3O(CH2)2O(CH2)2SH, EG2) for 24 h, we examined the surface structure and electrochemical behavior of the resulting EG2 SAMs using scanning tunneling microscopy (STM) and cyclic voltammetry (CV). STM observations clearly revealed that EG2 SAMs vapor-deposited on Au(111) at 298 K were composed of a disordered phase on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Interestingly, we found the coexistence of two structural phases: an ordered row structure (α-phase) and well-ordered and closely packed structure (β-phase), as shown in Figure 2 b. In addition, several vacancy islands (VIs) with a monatomic depth of 2.5 Å (dark trench areas) were observed on the surface, which were well-known intrinsic characteristics that appeared as a result of the formation of chemisorbed monolayers on Au(111) surfaces by the adsorption of S- or Se-containing molecules [ 1 , 2 , 3 , 4 , 5 , 11 , 14 , 48 , 49 , 50 ]. Note that the VIs were also fully covered with a monolayer, not a bare Au(111) surface, as already demonstrated via high-resolution STM observations for thiolate or selenolate SAMs on Au(111) [ 3 , 5 , 6 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, we found the coexistence of two structural phases: an ordered row structure (α-phase) and well-ordered and closely packed structure (β-phase), as shown in Figure 2 b. In addition, several vacancy islands (VIs) with a monatomic depth of 2.5 Å (dark trench areas) were observed on the surface, which were well-known intrinsic characteristics that appeared as a result of the formation of chemisorbed monolayers on Au(111) surfaces by the adsorption of S- or Se-containing molecules [ 1 , 2 , 3 , 4 , 5 , 11 , 14 , 48 , 49 , 50 ]. Note that the VIs were also fully covered with a monolayer, not a bare Au(111) surface, as already demonstrated via high-resolution STM observations for thiolate or selenolate SAMs on Au(111) [ 3 , 5 , 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the position and shape of RD peaks for SAM-covered Au electrodes were significantly influenced by the binding affinity between the anchoring group and the Au surface, the magnitude of van der Waals interactions between adsorbed molecules, and the degree of structural order of the SAMs [ 14 , 31 , 41 , 52 , 53 , 54 ]. To examine the electrochemical behavior of MEHA SAMs formed at different deposition times on Au(111), we measured the CVs of RD for MEHA SAM-modified Au electrodes, as shown in Figure 5 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations